HOPELESSNESS AMONG NURSING STUDENTS DURING THE EARLY PHASE OF COVID-19 PANDEMIC : ONLINE CROSS SECTIONAL STUDY AT UNIVERSITAS RESPATI YOGYAKARTA - Akbar Satria Fitriawan; Ririn Wahyu Widayati; Januar Rizqi; C.Riyan Alfrendo (Jurnal Keperawatan Respati Yogyakarta, 2023)
Background: Global pandemic of COVID-19 caused unprecedented effect in education sector due to the university closure and distance education, which could significantly affected students mental health and increased suicidality. Nursing students are vulnerable population due to already stressful academic activities coupled with pandemic loneliness and financial difficulties. Hopelessness, a negative view of the self in relation to the world and the future, identified as consistent predictor of suicidality. This study aimed to explore the prevalence of hopelessness among nursing students and association between sociodemographic characteristic and hopelessness. Methods: Online cross sectional study was conducted in Universitas Respati Yogyakarta between June until September 2020, and involved 232 nursing students that selected using consecutive sampling method. Sociodemographic questionnare and Beck Hopelessness Scale (BHS) were used to collect the data. Chi square test was used to analyze association between sociodemographic characteristic and hopelessness. Result: Our study elucidated that the prevalence of hopelessness among nursing students at Universitas Respati Yogyakarta during the early phase of COVID-19 pandemic is 9.5%. Chi square test revealed that there is no significant association between any sociodemographic characteristic and hopelessness (p>0.05). Conclusion: The prevalence of hopelessness among nursing students is low, and sociodemographic profiles is not determinant of hopelessness.